Pengaruh Umur Dan Pekerjaan Ibu Terhadap Kandungan Antioksidan Asi - Enggar; Alam, Gemini; Maddeppungeng, Martira (Jurnal Bidan Cendrawasih Palu, 2019)
Antioxidant is a compounds which can protect a baby from an oxidative stress and free radical hazard. Breast milk contains antioxidant and represents is the best food for a baby. This research animed at investigating the effect of women’s age and occupation on the breast milk antioxidant. The research used the cross sectional design with of 24 samples of the breastfeeding women who were selected using the purposive sampling technique. The respondents who were taken their breast milk samples were in healthy condition and were asked to become volunteers by contributing their breast milk in the sake of the research. The samples taken were the women who breastfed and had the babies ≤ 6 months old and fulfilled the inclusive and exclusive criteria. Oneway ANOVA analysis was used to perceive the effect of the women’s age and occupation on breast milk antioxidant. The research result indicates that the respondents’ age based on statistic test results is obtained the score of p= 0,563 ˃α=0,05 meaning that there is not significant effect between women’s age and breast milk antioxidant. The Respondent's occupation indicated the score of p= 0,055 ˃α=0,05 which means that there is no significant effect between the occupation and breast milk antioxidant. It is concluded that there is no effect of the women’s age and occupation on breast milk antioxidant. It is expected that the women who work outdoors can still give the breast milk. The women who can not give their breast milk directly can still give their breast milk by way squeezing.